Trends in Amplitude-Integrated Electroencephalography in the Smallest Preterm Neonates - Kristina Štuikienė; Elke Griesmaier; Ilona Aldakauskienė; Regina Vidmantė; Kastytis Šmigelskas; Rasa Tamelienė (MDPI AG, 2024)
Background. Amplitude-integrated electroencephalography is increasingly used for the neuromonitoring of premature infants. However, it is still not clear how bioelectrical activity changes in the smallest gestational age newborns. The aim of our study was to evaluate the bioelectrical activity of amplitude-integrated electroencephalograms in premature newborns of different gestational age to assess how gestational age and postnatal age influence patterns of amplitude-integrated electroencephalograms and to test the hypothesis of whether the bioelectrical activity of the brain matures faster after the birth of premature newborns than in utero. Methods. We prospectively included infants born before 32 weeks of gestational age between June 2020 and July 2022. Serial recordings of amplitude-integrated electroencephalograms were performed at three time points of age (days 1-3, 13-15, and 27-29). Recordings were analyzed for background patterns, the onset and appearance of cyclicity, and lower amplitude border and bandwidth, which were used to derive a composite Burdjalov score. Results. In total, 140 premature neonates were included in the study, and 112 of them completed the study. The median gestational age of the newborns enrolled in the study was 29 (27-30) weeks, and the mean weight was 1206 (350) g. Burdjalov scores increased with increasing gestational age. Higher scores were observed in every dimension of the amplitude-integrated electroencephalograms for newborns of lower gestational age when compared to newborns of higher gestational age of the same postmenstrual age. There was a significant correlation between gestational age and parameters of amplitude-integrated electroencephalograms at all time points. Conclusions. A higher gestational age has a positive effect on the bioelectrical activity of amplitude-integrated electroencephalograms. Increasing postnatal age affected amplitude-integrated electroencephalograms more than gestational age. Our hypothesis that the bioelectrical activity of the brain matures faster for premature newborns after birth than in the womb was confirmed.